Por amor al arte. Notas sobre la agalmatofilia y la Imitatio Creatoris, de Platón a Winckelmann - González García, Juan Luis (Anales de Historia del Arte, 2006)
With the story of Pygmalion, the classical embodiment of the «living image», the mythographers were allowed to compare the creative role of such a legendary character, capable of devising animated and rational beings, with the power of the gods. Besides this one, other accounts from Antiquity have come to us with the same blend of aesthetics, magic and technical skill, largely referred to Praxiteles and his most famous sculptures: the Aphrodite of Knidos and the Erotes of Parion and Thespiae. All these testimonies exemplify the so-called «love for statues», also known as «Pygmalionism» or more frequently as «Agalmatophilia». This paper analyses the main consequences of Agalmatophilia and Imitatio Creatoris: the power of the deus artifex, the bond between the artist and his creation, and the composite condition —half alive, half artificial— of the artefact produced. Through the Post-Classical Age, Agalmatophilia successively became an apologetic model to discourse on the dangers of idolatry; a moralising exemplum; a glorification of the genius and a claim for the debate on the paragone during the Renaissance and Baroque periods. In the 18th Century, by way of coda, the figure of Pygmalion would be praised as an allegory of the creative endeavour of the early Greek artists.